1994
DOI: 10.1108/00070709410076333
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Foodborne Infections in Europe and North America

Abstract: The frequency of reporting of foodborne infections of animal origin, in particular salmonella, campylobacter and Escherichia coli (VTEC) has increased in recent years due to changes in food production and processing methods in parallel with changes in eating habits and other social factors such as mass catering and the use of convenience foods. In contrast infections, primarily of human origin, in particular typhoid, paratyphoid and bacillary dysentery, are nowadays much less frequently associated with foodbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…Salmonella, Campylobacter and verotoxin-producing E. coli (e.g. E. coli O157:H7) (Sharp and Microbiological hazards 745 Reilly, 1994;van Logtestijn and Urlings, 1995). Within England and Wales the number of food poisoning notifications has risen steadily from approximately 15,000 cases reported in the early 1980s to over 60,000 cases reported in 1996, and the number of laboratory reports of Campylobacter and Salmonella has risen threefold (Djuretic, 1997).…”
Section: Is the Increase In Incidence Real?mentioning
confidence: 99%
See 2 more Smart Citations
“…Salmonella, Campylobacter and verotoxin-producing E. coli (e.g. E. coli O157:H7) (Sharp and Microbiological hazards 745 Reilly, 1994;van Logtestijn and Urlings, 1995). Within England and Wales the number of food poisoning notifications has risen steadily from approximately 15,000 cases reported in the early 1980s to over 60,000 cases reported in 1996, and the number of laboratory reports of Campylobacter and Salmonella has risen threefold (Djuretic, 1997).…”
Section: Is the Increase In Incidence Real?mentioning
confidence: 99%
“…changes in retailing practice and in social and household patterns of shopping and eating; and . a growing segment of the population which is especially vulnerable to infectious diseases (owing to immune impairment as a consequence of HIV infection, underlying chronic disease or ageing) (Lacey, 1993;van Logtestijn and Urlings, 1995;Altekruse and Swerdlow, 1996;Sharp and Reilly, 1994).…”
Section: Is the Increase In Incidence Real?mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that pathogenic bacteria can survive pH as low as 2.5 for 2 h or more (Benjamin & Datta, 1995;De Jonge, Takumi, Ritmeester, & Leusden, 2003;Gordon & Small, 1993;Lin et al, 1996). Furthermore, in the last decade a number of outbreaks of Escherichia coli O157:H7, Salmonella, Cryptosporidium and Norwalk virus infections associated with consumption of unpasteurized fruit juice have been documented in Europe, United States and other countries (Bresser, Lett, & Weber, 1993;CDC, 1997;Centers for Disease Control (CDC), 1999;Cody, Glynn, & Farrar, 1999; Cook, Dobbs, & Hlady, 1998;Millard et al, 1994;Sharp & Reilly, 1994;Singh, Kulshreshtha, & Kapoor, 1996). To prevent the risk of additional fruit juices-associated outbreaks, the US Food and Drug Administration (FDA) issued a rule in 2001 that requires fruit juice manufacturers to demonstrate that their manufacturing methods can achieve a 5-log10 reduction of foodborne pathogens (Food & Drug Administration, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…3). Occurrence rates and prevalence of foodborne diseases have been reported mostly by developed countries including USA, Canada, and Europe [6,[9][10][11][16][17][18] along with mortality and morbidity rates, magnitude, direction, and future trends [6,9,16,17,19,20]. Unfortunately, no reported data and long-term evaluations of foodborne diseases are available from developing countries (including Turkey) although these countries experience a rapid rate of population growth.…”
mentioning
confidence: 99%